Analisis Rekonsiliasi Fiskal Terhadap Laporan Keuangan Komersial Dalam Menghitung Pph Terutang PT XYZ (Jurnal Paradigma Akuntansi, 2022)
The purpose of this research is to analyze the financial statements of PT XYZ to determine whether the recognized income or expenses are in accordance with the applicable tax regulations and to find out the amount of Income Tax Payable at PT XYZ in 2018 after fiscal corrections are made. The subjects in this study were PT XYZ. The method used in this research is quantitative descriptive method. The data collection method used in this research is through library research and field research. The results showed that the preparation of fiscal financial reports at PT XYZ was not in accordance with the Income UU PPh No. 36 of 2008, because there are still fiscal correction errors for expenses that should be corrected so that it affects the errors in calculating the Payable Corporate Income Tax.